Does the Diversity of New Build Housing Type and Tenure Have a Positive Influence on Residential Absorption Rates? An Investigation of Housing Completion Rates in Leeds City Region. (8th August 2021) - Greenhalgh, Paul; McGuinness, David; Robson, Simon; Bowers, Kathryn
ABSTRACT: The research tests a proposition that a more diverse range of new build housing improves absorption rates. Land registry house sales for four Planning Authorities in Leeds City region in the UK, over an 11-year period, were used to calculate Brillouin's Index of diversity and perform Pearson and ANOVA tests to determine strength and significance of the correlation between absorption rates and diversity by type, size and tenure of new housing. The significant findings are that residential developments with higher diversity have lower absorption rates, conversely, developments with lower diversity have higher absorption rates and smaller sites are built-out faster.